THE ORGANIZATION OF TUTOR'S ACTIVITY IN THE SYSTEM OF DISTANCE EDUCATION AT HIGHER EDUCATIONAL ESTABLISHMENT - Voronkin, О.С. (Journal of Information Technologies in Education (ITE), 2016)
The article demonstrates the results of the online tutor’s activity components. The review of the interaction between the learners (content interaction and interpersonal interaction) in the distance course has shown that all of these elements should be taken into account in the course designing and should be later moderated by the tutor in the process of learning. It has been determined that effective learning occurs only in case of the possibility to sattisfy each student’s learning style. The complete learning circle should include different learning styles to follow the abovementioned requirements. According to the analysis of the online tutoring models the following structural components of tutor’s professional competence were defined: informative, organizational, psychological and pedagogical, technical, professional, personal, competence of online communication. Thus, in addition to the subject matter the tutor has to know psychological and pedagogical, organizational, methodological and technical bases of learning organization. The ability to plan (project) the expected final result of tutor’s activity and the readiness to learn new technologies appear particularly important. Different criteria and methods of evaluation of the effectiveness of tutor’s activity have been studied. It is shown that the estimation of the activity effectiveness should be based on the goals and the content of tutor’s activity, and it can be performed by quantitative and qualitative methods. Quantitative method permits collecting the data which can be analyzed statistically. The qualitative method is more subjective, flexible and dynamic. The paper states the currency of the requirement of online tutors training programs on the state level.